(untitled) (Pakistan Journal of Science, 2022)
In this study, geographical information system (GIS) techniques used to study the relief structure for slope, aspect, hill shade, contours and generation of Digital Terrain Model (DTM) of Southern Haripur Tehsil. Remotely sensed data of Shuttle Radar Topographic Mission (SRTM), Digital Elevation Model (DEM) data having 90 by 90 meter resolution of USGS was used for the terrain analysis. In this study it was found out that the northern area of Haripur was higher in elevation and south eastern slope was gentle and having less height. Central area of Haripur district was found almost flat. South western part of the district had less height. The northern slopes were steep and higher in elevation and southern slopes were gentle and lower in height. It was also observed that the north eastern area of Southern Haripur Tehsil was extremely vulnerable for land sliding due to steep slopes, high elevation and fragile geology. This study illustrated that the GIS techniques were more effective for terrain information.